Seed-mediated liquid phase deposition method for TiO2 nanostructure growth on ITO substrate: Effect of surfactant - Roza L.; Umar A.A.; Rahman M.Y.A.; Salleh M.M. (2023)
This paper reports the study on the effect of the surfactants, cetyltrimethylammonium bromide (CTAB) and hexamethylenetetramine (HMT) on the growth of TiO2 nanostructures on ITO surface. TiO2 nanostructures were prepared using a seed-mediated liquid phase deposition (LPD) method. LPD is an electrolysis deposition of metal oxide via hydrolysis of metal-fluoro complex in the presence of boric acid at ambient temperature. In typical case, this method allows the formation of metal oxide film on the substrate surface. Since the properties strongly depend on shape at this length scale, the morphology control growth of TiO2 nanostructures is highly demanded in order to produce desired properties in application. In this work we demonstrate the growth of wire like structure of TiO2 (instead of film) on ITO surface via a seed-mediated liquid phase deposition in the present of surfactant. In typical result, TiO2 with diameter ca. 40 nm at the bottom of nanowire to ca. 10 nm at the nanowire tip can be successfully grown on the surface. The effect of surfactant and their concentration on the growth characteristics of TiO2 nanostructure will be discussed.